1980
DOI: 10.1093/jn/110.3.469
|View full text |Cite
|
Sign up to set email alerts
|

Total True Efficiency of Zinc Utilization: Determination and Homeostatic Dependence upon the Zinc Supply Status in Young Rats

Abstract: Total true efficiency of zinc utilization and its component factors, true absorption and metabolic efficiency, were studied in relation to dietary zinc supply in a 15-day experiment with 36 weanling rats in six groups. After day 3, the initial supply of 18.2 ppm zinc in the diet for all groups was changed to 5.6, 10.6, 18.2, 39, 70 and 141 ppm in groups 1 to 6, respectively. During the 6-day balance period after day 9, zinc intake was proportional to dietary zinc concentration. Mean daily rates of weight gain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
42
0
1

Year Published

1984
1984
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(47 citation statements)
references
References 27 publications
4
42
0
1
Order By: Relevance
“…These results would suggest that the major differences in zinc bioavailability among different zinc sources can be attributed to dif- Sahraei et al: Estimation of Zinc Sources for Broilers 57 RBV (%) c ferences in absorption, and that once absorbed, differences in zinc utilization among sources reflect differences in net utilization. These differences in utilization may reflect differences in endogenous zinc loss, which has been shown to increase due to homeostatic mechanisms with increasing zinc absorption (Weigand and Kirchgessner, 1980). In poultry and swine nutrition, it is difficult to avoid the presence of phytates as they are the main storage forms of P in seeds.…”
Section: Discussionmentioning
confidence: 99%
“…These results would suggest that the major differences in zinc bioavailability among different zinc sources can be attributed to dif- Sahraei et al: Estimation of Zinc Sources for Broilers 57 RBV (%) c ferences in absorption, and that once absorbed, differences in zinc utilization among sources reflect differences in net utilization. These differences in utilization may reflect differences in endogenous zinc loss, which has been shown to increase due to homeostatic mechanisms with increasing zinc absorption (Weigand and Kirchgessner, 1980). In poultry and swine nutrition, it is difficult to avoid the presence of phytates as they are the main storage forms of P in seeds.…”
Section: Discussionmentioning
confidence: 99%
“…Coppen and Davies [3] fed zinc-controlled diets to young rats, and found that 65 Zn absorption decreased from 99% for 5-mg Zn/kg diet to 56% for 160-mg Zn/kg diet. Similar findings have also been reported by several other investigators [5,12], however, many efforts were made under zinc deficiency or relatively low levels of dietary zinc. Our results indicate that zinc absorption can be regulated over a wide range of dietary zinc, not only in relatively low levels as previously reported.…”
Section: Discussionsupporting
confidence: 90%
“…The methods for enhancing the excretion of radionuclides from the body can be classified into four groups: (1) combining the radionuclide with a chelating agent, (2) diluting the radionuclide with its stable isotopes, (3) combining the radionuclide with adsorbents in the gut, (4) disturbing the metabolism with hormones. Although a chelating agent, diethylenetriaminepentaacetic acid, is recommended for the elimination of 65 Zn, we noted the dilution method because zinc is an essential trace element and its homeostasis is maintained by regulating the absorption and excretion [1,3,5,12]. The present experiment was designed to estimate the efficacy of zinc addition to diet for preventing the gastrointestinal absorption of 65 Zn and for enhancing its excretion from the body.…”
mentioning
confidence: 99%
“…Zinc is mainly excreted into feces via the pancreatic juice and intestinal mucosal cells [8]. Endogenous fecal excretion of zinc increases as dietary zinc intake increases [18], and zinc concentrations in various tissues are maintained homeostatically over a wide range of dietary zinc levels [1,14]. These observations suggest that animals have a high potential for excreting excess zinc from the body.…”
Section: Discussionmentioning
confidence: 99%